PRODUCTION of AROMATIC BRAN USING LIQUID ORGANIC SUPPLEMENT of COW MANURE EFFECTS ON LACTIC ACID, pH, DRY MATTER LOSS and FLEIGH VALUE (NF) - Suryadi, Annisa Suci Ghifaryz (Unpad Press, 2024)
This study aims to determine the effect of different doses of liquid organic supplements made cow manure added to rice bran to produce aromatic rice bran with the best values in terms of lactic acid, pH, dry matter loss, and Fleigh Value (NF). The research was conducted from May - June 2024 at the Ruminant Nutrition and Animal Feed Chemistry Laboratory, Faculty of Animal Science, Padjadjaran University. This experimental study employed a Completely Randomized Design with 3 treatments and 6 replications, P0 = 1 kilogram of bran + 300 grams of molasses, P1 = 1 kilogram of bran + 200 grams of molasses + 100 mL of SOC, and P2 = 1 kilogram of bran + 100 grams of molasses + 200 mL of SOC. Data analysis was using Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test. The results showed that the use of cow manure SOC affected the pH, lactic acid content, and dry matter loss of aromatic rice bran, but did not affect the Fleigh Value (FV). The application of SOC with a dose of 100 grams of molasses + 200 mL SOC produced high lactic acid (21.12%), the lowest pH value (4.52), dry matter loss (8.21%), and a Fleigh value of (167.59%).